2013
DOI: 10.3402/jchimp.v3i1.20240
|View full text |Cite
|
Sign up to set email alerts
|

CT pulmonary angiography: an over-utilized imaging modality in hospitalized patients with suspected pulmonary embolism

Abstract: AimsTo determine if computed tomographic pulmonary angiography (CTPA) was overemployed in the evaluation of hospitalized patients with suspected acute pulmonary embolism (PE).MethodsData were gathered retrospectively on hospitalized patients (n=185) who had CTPA for suspected PE between June and August 2009 at our institution.ResultsCTPA was done in 185 hospitalized patients to diagnose acute PE based on clinical suspicion. Of these, 30 (16.2%) patients were tested positive for acute PE on CTPA. The Well's pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In recent years, CTPA has replaced PA as the gold standard for the diagnosis of PE [ 2 ]. It has been reported that the use of CT scan has increased from 3 to 70 million between 1980 and 2007 [ 11 ]. Whereas in patients undergoing CTPA for suspected PE, the prevalence of PE is only 5% to 10% in America and 20% to 30% in Europe [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, CTPA has replaced PA as the gold standard for the diagnosis of PE [ 2 ]. It has been reported that the use of CT scan has increased from 3 to 70 million between 1980 and 2007 [ 11 ]. Whereas in patients undergoing CTPA for suspected PE, the prevalence of PE is only 5% to 10% in America and 20% to 30% in Europe [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is associated with an increased risk of radiation exposure [ 2 , 4 , 5 ]. In the United States, 1.5%-2.0% of malignant tumors are associated with CT scan and the incidence of contrast-induced nephropathy after having CTPA in patients suspected of PE is up to 12% [ 11 ]. Therefore, we have a responsibility to find new diagnostic tools to reduce the number of unnecessary CTPA, such as TLS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 , 6 Because of its low specificity for VTE, D‐dimer is limited to ruling out VTE in low‐probability cases, whereas diagnostic imaging is necessary to rule out or confirm diagnosis in medium‐ or high‐probability cases. With less than 20% of computed tomography pulmonary angiograms performed on suspicion of PE confirming the diagnosis, 7 , 8 , 9 more specific biomarker‐based tools implemented in the diagnostic workup have potential to reduce unnecessary imaging. Several studies have proposed biomarker candidates for acute VTE (e.g., p‐selectin, microRNAs), 10 , 11 but none have yet translated to clinical implementation.…”
Section: Introductionmentioning
confidence: 99%